THE ROLE FOR NATURALLY OCCURRING VARIANTS OF LISTERIA MONOCYTOGENES INVASION FACTORS IN PERINATAL LISTERIOSIS - K. A. Sobyanin; E. V. Sysolyatina; Ya. M. Chalenko; A. Ya. Lavrikova; E. V. Kalinin; V. I. Pushkareva; S. A. Ermolaeva (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
Aim. Using the model of intragastric Listeria monocytogenes infection in pregnant mice to compare an input of found in nature variants of the invasion factor InlB in perinatal listeriosis. Materials and methods. Mice on 12-16 days of pregnancy were injected intragastrically with 108 CFU of isogenic recombinant L. monocytogenes strains EGDeAinlB::InlB9 and EGDeAinlB:: InlB14. The strains expressed naturally occurring InlB variants, InlB9 and InlB14. In 72 h, mice were subjected to euthanasia to evaluate bacterial loads in the internal organs. Results. Only the strain, which expressed InlB14, caused perinatal infection. Microbial loads in the liver, spleen and Peyer’s patches was 715, 315 and 70 times higher for this strain than for the strain EGDeAinlB:: InlB9 (p